2020
DOI: 10.32479/ijeep.9336
|View full text |Cite
|
Sign up to set email alerts
|

Energy Sustainability, Energy Financing and Economic Growth in Nigeria

Abstract: Increase in the global population growth has led to a simultaneous increased in demand for energy leading to increased fear of global warming. This situation has given the international community a cause for concern and as a result, countries are seeking alternative sources for cleaner and sustainable energy. The importance of utilising greener energy sources is evident in the United Nation's Sustainable Development Goals (SDGs), especially Goal 7, Target 2. This study examined the long-run relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Chirambo (2016) argued that inability of countries in Africa to secure adequate investment constituted a major setback for the continent to access clean energy. Onabote et al (2021) established a long run convergence among various sources of sustainable energy and economic growth in Nigeria. Mitic, Ivanovic and Zdravkovic (2017) utilized Dynamic Ordinary Least Squares (DOLS and Fully Modified OLS (FMOLS) techniques in assessing the linkage between carbon emissions and the growth of 17 emerging economies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Chirambo (2016) argued that inability of countries in Africa to secure adequate investment constituted a major setback for the continent to access clean energy. Onabote et al (2021) established a long run convergence among various sources of sustainable energy and economic growth in Nigeria. Mitic, Ivanovic and Zdravkovic (2017) utilized Dynamic Ordinary Least Squares (DOLS and Fully Modified OLS (FMOLS) techniques in assessing the linkage between carbon emissions and the growth of 17 emerging economies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Building the model for the estimation of the nexu between clean energy supply and industrial development in Nigeria requires some insights to be drawn from the works of Onabote et al (2021), Osabohien et al (2021) and Olaoye et al Some modification was however done on the adapted model to suit the objective of this study. Therefore, the model is as enunciated;…”
Section: Model Specificationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study provided evidence that energy consumption is critical in the evolution of the Nigerian economy. Onabote et al (2020) examined the relationship existing between energy sustainability, financing and economic growth of Nigeria from 1981 to 2014. The study established a long to zrun relationship and also found the energy sustaining and financing variables affecting economic growth differently.…”
Section: Carbon (Co 2 ) Emissionsmentioning
confidence: 99%
“…In Nigeria, Electricity is in high demand and critical to the operations of all economic sectors. The fact is that the energy sources in Nigeria are non-renewable and challenging to sustain (Onabote et al, 2020). The bigger the energy ingestion, the more the carbon (CO 2 ) discharge emanating from absorption of relic energy (oil and gas).…”
Section: Introductionmentioning
confidence: 99%